Poison or panacea: a decade of parliamentary discourse on cannabis regulation in Slovenia = Strup ali lek : desetletje parlamentarnih razprav o regulaciji konoplje v Sloveniji - Čufar, Kristina (Revija za kriminalistiko in kriminologijo, 2024)
Cannabis is the most prevalent controlled substance in Slovenia, and its legal status is fraught with controversy. In the past decade, several legislative proposals unsuccessfully attempted to transform the regulation of industrial, medical and non-medical cannabis. This article employs critical discourse analysis of parliamentary discourse on the proposed changes to cannabis regulation in the National Assembly of the Republic of Slovenia from 2013 to 2024. It identifies the discourse participants’ main narratives and maps the social power relations involved in cannabis regulation. The proponents of less stringent regulation of cannabis initially relied on the fantastic narrative emphasising the magical properties of cannabis, but later adopted the compassionate narrative, accentuating the suffering of medical patients with difficulties in accessing cannabis. The opponents of regulatory change have adopted the public health narrative stressing the dangers of cannabis use and the virtues of cannabis prohibition. The public health narrative is occasionally displaced by the moral panic narrative asserting the threat of moral deterioration, widespread lethargy, etc., as consequences of greater cannabis availability. All discourse participants use the economic narrative, highlighting either fiscal gains or costs, while the once-leading criminality narrative is effectively absent in the parliamentary discourse on cannabis. The analysis shows that cannabis is primarily framed as a public health issue, with public health experts emerging as the dominant force in parliamentary cannabis discourse. Despite broad mobilisation to change cannabis regulation, the status quo remains undisturbed.